Metabolomic Characteristics of Fatty Pancreas - Jaghutriz, Benjamin Assad; Wagner, Róbert; Heni, Martin; Lehmann, Rainer; Machann, Jürgen; Stefan, Norbert; Häring, Hans-Ulrich; Fritsche, Andreas (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Pancreatic steatosis is associated with impaired beta cell function in patients with prediabetes. The pathomechanisms underlying this association still remain to be elucidated. Recent data show that adipocytes are situated within the pancreatic parenchyma and therefore give raise to hypothesize that pancreatic fat together with known and unknown metabolites such as hepatokines affect insulin secretion. Applying a targeted metabolomic approach we investigated possible circulating markers of pancreatic fat in order to better understand its role in the pathophysiology of impaired beta cell function.Methods We included 361 Caucasians, at increased risk of type 2 diabetes, from the Tübingen Family Study. All participants underwent a frequently sampled oral glucose tolerance test to assess insulin secretion and a magnetic resonance imaging to quantify pancreatic fat content, total body fat and visceral fat. Among the 152 subjects with prediabetes (IFG and/or IGT), two groups each with 20 individuals, having the lowest and highest pancreatic fat content were selected. The groups were matched for sex, age, BMI, total fat content, visceral fat content, liver fat content and insulin sensitivity. Metabolites were analyzed using the AbsoluteIDQ® p400 HR Kit by Biocrates.Results Pancreatic fat content of all 152 subjects with prediabetes was negatively associated with insulin secretion represented by AUCC-peptide 0–120/AUCGlucose 0–120 (p=0.04; β=− 3.24). Furthermore, pancreatic fat content was positively associated with BMI, total body and visceral fat (all p<0.005). Levels of aminoacids, biogenic amines and monosaccharides were similar between the groups with high/low pancreatic fat content (p>0.90). Also, levels of polar lipids such as lysophosphatidylcholines, phosphatidylcholines, sphingomyelins and ceramides did not differ significantly between the groups (p>0.90). Investigating the levels of neutral lipids such as aclycarnitines, diglycerides, triglycerides and cholesteryl esters also revealed no differences between the groups (p>0.90).Conclusion The amount of pancreatic fat is not associated with the metabolomic pattern in individuals with prediabetes. This might be due to the relatively low pancreatic fat content compared to the total amount of fat stored in other depots. The impact of pancreatic steatosis on insulin secretion might be mediated by paracrine effects which cannot be detected in the circulation.
Keywords: prediabetes; type 2 diabetes; pancreatic fat; non-alcoholic fatty pancreas disease; NAFPD; metabolomics; insulin secretion; insulin sensitivity